Methods of evaluation of the quality of life in rheumatic diseases - Jankowska-Polańska, Beata; Polański, Jacek (Reumatologia/Rheumatology, 2014)
The concept of health assessment for a patient is identified with functional status and quality of life in a disease. The obtained results indicate that the assessment made by the patient often differs from the assessment by the physician. In rheumatology the goal of therapy is to achieve remission of the disease or low activity, but it is not always possible. Assessment of own health allows a patient to be actively involved in the implementation of a treatment processes. The patient’s subjective evaluation of health status is a practical factor which may contribute to improving the quality of care provided. The results of the assessment will serve as a guide to planning of professional nursing care for patients. The simultaneous assessment of the health and quality of life it is possible to carry out only with the use of standardized research tools.